Developmental toxicity of Zishen Guchong Pill on the early life stages of Zebrafish - Jiazhen Wang; Cailian Mo; Pengfei Tu; Na Ning; Xin Liu; Shenghua Lin; Sellamani Muthulakshmi; Zixin He; Yun Zhang; Kechun Liu; Qiuxia He (Elsevier, 2021)
Background: Zishen Guchong Pill (ZGP), a traditional oriental herbal medicine, has been applied broadly in the treatment of threatened or recurrent miscarriages in clinics, but little is known about its developmental toxicity.Aim of the study: This study aimed to investigate the potential toxicity of ZGP and its mechanisms.methods: We investigated the developmental toxicity of ZGP using a zebrafish model. Zebrafish embryos at 4 hours post-fertilization (hpf) were exposed to 25, 50, 100, and 200 µg/mL ZGP until 120 hpf. The zebrafish morphology, organ development, reactive oxygen species (ROS) content, oxidative stress-related enzyme activity, and mRNA levels of oxidative stress and apoptosis-related genes were measured.Results: Our results demonstrated that ZGP had no toxicity at 50 µg/mL ZGP but induced phenotypic defects and decreased the hatching rate and body length at more than 50 µg/mL ZGP (high dose). High doses of ZGP caused severe heart failure, including a significant increase in the sinus venosus (SV) and bulbus arteriosus (BA) distance and pericardial area, and reduced heart rate and numbers of red blood cells. In addition, high doses of ZGP caused liver atrophy and decreased the length of dopamine ganglia and neurovascular. High doses of ZGP elicited the generation of ROS and elevated malondialdehyde levels, but reduced the activity of superoxide dismutase (SOD) and catalase (CAT). Real-time PCR data showed the downregulation of oxidative stress-related genes (sod and cat) and the activation of Nrf2 (nrf2, keap1, ho-1, nqo1, gclc, and gclm) and P53 (p53, bcl-2, and bax) signal pathway genes after high ZGP exposure.Conclusions: Taken together, our results indicate that ZGP has no developmental toxicity under 50 µg/mL ZGP but induced developmental toxicity in zebrafish embryos at more than 50 µg/mL ZGP, and oxidative stress contributed to the toxic response. • ZGP is safe and reliable in clinical use. • ZGP (high does) caused an increase in ROS, which induced oxidative stress, leading to apoptosis and developmental toxicity. • The Nrf2 signaling pathway is impaired during the early stages of ZGP-induced developmental toxicity.